2006 25th International Conference on Thermoelectrics 2006
DOI: 10.1109/ict.2006.331326
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nanostructures in Thermoelectric Pb-Te-Sb Alloys

Abstract: In analogy to recent demonstrations of enhanced thermoelectric properties in superlattice materials, composite structures with nanoscale features promise dramatic improvements in the figure of merit of thermoelectric materials. Fabrication of nanostructured thermoelectric materials via bulk synthesis is an attractive route for commercial applications. Nanometer scale lamellae of PbTe and Sb 2 Te 3 form when quenched eutectic PbTe-Sb 2 Te 3 melt is subsequently annealed. The lamellar spacing depends on the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Here, γ is the surface energy, T E is the eutectoid invariant temperature, Δ T and Δ H are the temperature and enthalpy difference of the supercooled material at the point of nucleation compared to T E , and V m is the molar volume. The increase in interlamellar spacing with time evident in Figure is clearly expected from these relationships, although the linear dependence with time cannot be verified . Its increase with temperature suggests that λ 0 strongly depends on temperature, most likely via its dependence on Δ T .…”
mentioning
confidence: 78%
“…Here, γ is the surface energy, T E is the eutectoid invariant temperature, Δ T and Δ H are the temperature and enthalpy difference of the supercooled material at the point of nucleation compared to T E , and V m is the molar volume. The increase in interlamellar spacing with time evident in Figure is clearly expected from these relationships, although the linear dependence with time cannot be verified . Its increase with temperature suggests that λ 0 strongly depends on temperature, most likely via its dependence on Δ T .…”
mentioning
confidence: 78%
“…It was also found that with excess Pb and/or Sb precipitated phases in PbTe the thermal conductivity was suppressed and power factor was effectively enhanced [4,20]. Utilizing the eutectic decomposition in the pseudo-binary PbTe-Sb 2 Te 3 system Snyder et al successfully produced a layer-by-layer self-assembled nanostructure [21][22][23]. Poudeu et al [24] found that the introduction of Sb into Pb 9.6 Te 10−x Se x solid solutions which are rich in chalcogen elements caused an extremely low thermal conductivity and hence good TE performance due to the formation of Sb-rich nanocrystals.…”
Section: Introductionmentioning
confidence: 99%